Driving farmer-led climate action: EAFF's climate achievements (2021-2025) - Eastern Africa Farmers Federation (2025)
The Eastern Africa Farmers Federation (EAFF) has worked deliberately to integrate climate change into its core agenda, equipping farmer organisations with knowledge, shaping debates on policy and negotiations, and building partnerships that place farmers at the centre of climate solutions. Between 2021 and 2025, this shift has positioned the EAFF as a well-recognised voice in regional, continental, and global discussions on agriculture, climate adaptation, and food systems transformation and resilience. This brief provides a summary on the EAFF’s climate change work, documenting their activities, achievements and the partnerships that have enabled their progress.